Cyclical Crude Oil Price Movements and the Nigerian Growth Dynamics: An Empirical Approach - Obuareghe, Goddey; Orubu, Christopher, O.; Awogbemi, Titus, O. (Pancasila International Journal of Applied Social Science, 2025)
The paper examined the effect of cyclical crude oil price movements on the Nigerian economic dynamics, emphasizing empirics. The study spanned from 1989 to 2021. This is in view of evaluating how cyclical oil, petrol, diesel, and kerosene price movements impact real gross domestic products in Nigeria. Data for the analysis were obtained from the Central Bank of Nigeria (CBN) Bulletin and the World Bank database from 1989 to 2021, i.e. 33 years. The data analysis methods adopted are the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) and Vector Auto-regressive models. The study evidenced that cyclical movements in oil and diesel prices significantly reduce Nigeria's economic growth. In contrast, cyclical movements of petrol and Kerosene prices minimally improve the Nigerian economy's growth. Hence, the study concludes that cyclical movements in oil and diesel prices counter-productive to the Nigerian economy. Consequently, the Nigerian government should ensure that proceeds from oil products should be channelled to priority sectors of the Nigerian economy. Lastly, the ongoing debates on the diversification of the Nigerian economy need to be re-evaluated.